A Faculty Development Workshop for High-Value Care Education Across Clinical Settings - Lisa E. Herrmann; Michael Tchou; Jimmy Beck; Maya Dewan; Carolyn Avery; Adam Schickedanz; Ricardo Quinonez; Lauren Walker (Association of American Medical Colleges, 2018)
Introduction Despite rising health care costs, trainees frequently do not receive formal high-value care (HVC) training. As medical education often occurs through informal learning, it is imperative that medical educators be prepared to teach HVC concepts across clinical settings. Methods This workshop was created to provide frameworks for teaching HVC across four pediatric educational settings: (1) case-based conferences, (2) inpatient rounding, (3) ambulatory visits, and (4) conversations with patients and families. Frameworks were developed based on literature review, content experts' knowledge, and internal assessment and feedback. The workshop was divided into two sections: a didactic overview of HVC education and interactive small-group sessions to practice application of the Toolkit for Teaching High-Value Care. At the end of the workshop, participants completed the Prescription for High-Value Care to create a personal action plan. Results This workshop has been presented at both national and local pediatric conferences. From over 89 evaluations (83% response rate), participants felt the workshop met objectives, served as a valuable use of their time, and provided useful resources. Evaluations elicited specific actions that participants gleaned from workshop content along with proposed behavior changes, such as creating HVC case-based conferences at their home institution and initiating more value-based discussions. Discussion This workshop has been successfully presented in both national and local settings and has been well received by participants. The workshop is targeted for clinical educators and aims to address the gap in faculty development for HVC education.